DIGITAL DIPLOMACY AS A MEANS OF STRATEGIC STATE COMMUNICATION - Kononenko, Valery; Komarova, Tetiana (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The problem of digital diplomacy as a means of strategic communication of the state is considered. The authors consider different approaches to defining this phenomenon. Digitization of social processes affects diplomacy and its practical implementation. The changes concern institutions and mechanisms through which states and other international actors realize their interests. Attention is paid to such components of modern diplomacy as large volumes of information and databases, e-government, e-participation, cyber security, and digital transformation. The article combines an analytical view of modern diplomacy with the disclosure of the conditions of the information age, which shape the directions and fundamental tasks of modern development. It was determined that transformations of power regarding the priority of production and control of value meaning and cultural codes of society, should be taken into account by digital diplomacy, with the involvement of a wide range of subjects from both the state and non-state spheres. The article is devoted to the specific issues of challenges to political decision-making processes in the field of digital diplomacy: virtualization of social and political processes, the state of uncertainty, instability, fluidity in the global space, latency, uncoordinated influence of centers of power (power), the circle of which has significantly expanded, the struggle for informational dominance, for reducing the information space and opportunities of opponents. The authors note that knowledge, values, cultural codes of societies, communication channels, new media, and information networks are becoming strategically significant in international activities. Since the new quality of power is that it increasingly gets rid of institutional localization, anonymity, network flexibility, capacity for non-linear policy-making, principles of horizontality and verticalism, taking into account the tasks of the unstable balance of the principles of horizontality and verticalism, strategic and tactical, priority and conjunctural tasks, axiological meanings, and competitive images give modern actors of world politics great advantages.